The Business Leaders' Pulse: An online business survey - Tony Chernis; Chris D'Souza; Kevin MacLean; Tasha Reader; Joshua Slive; Farrukh Suvankulov (Bank of Canada, 2022)
The Business Leaders' Pulse is a new online survey conducted each month. It is designed to provide timely and flexible input into the Bank of Canada's monetary policy decision making while also creating a platform to analyze business conditions and uncertainty. Since May 2021, the Bank has been reaching out to leaders of almost all types of businesses across the country with this short questionnaire inquiring about their sales and employment growth expectations, the risks to their business outlook, and topical questions that address specific information needs of the Bank. This survey is designed to complement the Bank's quarterly Business Outlook Survey conducted in person. The Business Leaders' Pulse has already proven valuable in getting timely feedback from firms about the effects of a rapidly changing economic environment, including the impact of COVID-19 and the Russian invasion of Ukraine. It has also helped Bank staff assess the extent of and reaction to ongoing economic challenges, such as supply chain bottlenecks and labour shortages.
Keywords: C83; D22; E32; 330; Monetary policy and uncertainty; Recent economic and financial developments